2015
DOI: 10.1504/ijssci.2015.074218
|View full text |Cite
|
Sign up to set email alerts
|

Co-creation in living labs: exploring the role of user characteristics on innovation contribution

Abstract: Since the 1970s, the innovative potential of users has been recognized by von Hippel and his seminal works on the Customer Active Paradigm (CAP) and Lead Users. This fostered further research into the nature of user contribution in NPD and the characteristics of innovative and innovating users. This research stream has been labeled 'user innovation' and looks at the utility gains for end-users when involved in innovation. More recently, open innovation approaches have been looking to integrate the insights and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…The second case implemented and evaluated pervasive citizen participation, and the third case involved co-creators for urban mobility solutions through combining social and economic (technological) innovations. Additionally, Schuurman et al (2015) assessed relationships between user characteristics and user contributions for three case studies. In the first case study named "iCinema", they invited stakeholders from the movie industry to explore interactive cinema formats.…”
Section: Living Lab Approachesmentioning
confidence: 99%
“…The second case implemented and evaluated pervasive citizen participation, and the third case involved co-creators for urban mobility solutions through combining social and economic (technological) innovations. Additionally, Schuurman et al (2015) assessed relationships between user characteristics and user contributions for three case studies. In the first case study named "iCinema", they invited stakeholders from the movie industry to explore interactive cinema formats.…”
Section: Living Lab Approachesmentioning
confidence: 99%
“…An important origin of the concept of co-creation is research on innovation methodology, in which it was found that the quality (value) of inventions and other solutions benefits from suggestions and active input from users (customers) [52][53][54]. The prominent presence of co-creation in living labs comes with the issue to what extent it is driven in formal ways (e.g., procedural time planning) or informally [3,22,32]. If the last is true, co-creation tends to be the result of spontaneous self-organization, which could enhance speed of the learning processes, but could also exclude specific users.…”
Section: Participation and Co-creationmentioning
confidence: 99%
“…As earlier indicated, the involvement of adequately selected user-groups is critical as an input, representing citizens or other users affected by the problem but also owning capabilities/skills that match with living labs learning practices, like using simulation tools and scenario thinking [23,24]. In addition, user involvement should take place early in the process and should be sufficiently intensive and rich in terms of multiple experimentation and switching roles [1][2][3]55,59]. However, there is a dilemma involved in selection of participants and wider stakeholders.…”
Section: Urban Living Labs Learningsmentioning
confidence: 99%
See 1 more Smart Citation
“…This perception is in line with Battisti (2012) on the need to adopt a new model for the analysis of social innovation, to deal with the user needs and the necessary collaboration between relevant social groups as active participants in the co-solution of complex problems and social rights. The co-creation in living labs is an emerging theme and has been studied in different fronts, such as the role of user characteristics in innovation contribution (Schuurman et al, 2015), the connections between interested parties in the development of innovations (Greve, Martinez & Neely, 2017) instruments to support co-creation and user involvement (Beutel, Jonas & Moeslein, 2017;Haukipuro, Väinämö & Hyrkäs, 2018).…”
Section: Open Social Innovationmentioning
confidence: 99%